2009
DOI: 10.1038/ijo.2009.46
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and characterization in primary culture of white adipose tissue brown adipocyte-like cells

Abstract: Background: Rodent brown adipose tissue (BAT) is considered the main effector of adaptative thermogenesis as it contains a unique mitochondrial uncoupling protein, termed as uncoupling protein-1 (UCP1). The emergence of ectopic brown adipocytes in the white adipose tissue (WAT), called recruitment, might play an important role in the prevention of obesity. The recruitment phenomenon has until now been investigated mostly in vivo. Objectives: This study is an attempt to mimic in vitro the recruitment phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
3
25
0
1
Order By: Relevance
“…Because both apelin and APJ are abundantly expressed in white adipocytes (24, 59), we sought to investigate apelin's effects on browning of white adipocytes. Consistent with previous studies (13,60), it was found that UCP1 expression in human white adipocytes is much lower than in brown adipocytes (Fig. 5).…”
Section: Apelin Stimulates Expressions Of Brown Adipogenic and Thermosupporting
confidence: 92%
“…Because both apelin and APJ are abundantly expressed in white adipocytes (24, 59), we sought to investigate apelin's effects on browning of white adipocytes. Consistent with previous studies (13,60), it was found that UCP1 expression in human white adipocytes is much lower than in brown adipocytes (Fig. 5).…”
Section: Apelin Stimulates Expressions Of Brown Adipogenic and Thermosupporting
confidence: 92%
“…These results suggested that the changes from white adipocytes to beige ones might not be a result of differentiation but simply a change to a high-performance type of cell. Several studies had suggested that beige adipocytes were a kind of white adipocyte [35] [36], findings which supported our own. However, the transgenic brown adipocytes expressing the PRDM16 gene at a high level [16] showed stable characteristics, and natural brown adipocytes taken from the body might also be stable.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro, RA increased 1 . 6 times UCP-1 mRNA expression in the BAT and slightly decreased its expression in WAT adipocytes (68) . In addition to the UCP-1 gene transcription, RA has been found in vitro to decrease preadipocyte survival time and to inhibit or promote adipose cell differentiation depending on the dose, probably regulated by RA intracellular lipid-binding protein-II (59,(69)(70)(71)(72) .…”
Section: Vitamin a And The Adipose Tissuementioning
confidence: 86%